2021
DOI: 10.3390/antibiotics10020182
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Patterns and Antibiotic Use during Hospital Conversion in the COVID-19 Pandemic

Abstract: Objective: To describe empirical antimicrobial prescription on admission in patients with severe COVID-19, the prevalence of Hospital-Acquired Infections, and the susceptibility patterns of the causing organisms. Methods: In this prospective cohort study in a tertiary care center in Mexico City, we included consecutive patients admitted with severe COVID-19 between March 20th and June 10th and evaluated empirical antimicrobial prescription and the occurrence of HAI. Results: 794 patients with severe COVID-19 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 28 publications
3
44
0
3
Order By: Relevance
“…Therefore, from the start of the pandemic, doctors treating COVID-19 patients have been prone to prescribe antibiotics empirically on admission to hospital (Abelenda-Alonso et al, 2020). As such, up to 56-92% of hospitalized COVID-19 patients were given antibiotics throughout the course of treatment, although only around 6-15% of them actually suffered bacterial co-infection (Li et al, 2020;Vaughn et al, 2020;Martinez-Guerra et al, 2021). A retrospective study from the Wuhan Union Hospital revealed that the majority of patients with secondary bacterial infections had acquired antimicrobial resistant strains (carbapenem-resistant K. pneumoniae, A. baumannii; methicillin-resistant S. aureus) (Li et al, 2020).…”
Section: Perspectivementioning
confidence: 99%
“…Therefore, from the start of the pandemic, doctors treating COVID-19 patients have been prone to prescribe antibiotics empirically on admission to hospital (Abelenda-Alonso et al, 2020). As such, up to 56-92% of hospitalized COVID-19 patients were given antibiotics throughout the course of treatment, although only around 6-15% of them actually suffered bacterial co-infection (Li et al, 2020;Vaughn et al, 2020;Martinez-Guerra et al, 2021). A retrospective study from the Wuhan Union Hospital revealed that the majority of patients with secondary bacterial infections had acquired antimicrobial resistant strains (carbapenem-resistant K. pneumoniae, A. baumannii; methicillin-resistant S. aureus) (Li et al, 2020).…”
Section: Perspectivementioning
confidence: 99%
“…Effective diagnostic specimens for conducting mass testing and for accurate diagnosis of COVID-19 is critical and deemed necessary [14]. The inappropriate use of antibiotics during the COVID-19 pandemic may further worsen the situation in relation to antimicrobial resistance [15][16][17]. An assessment to determine changes in antimicrobial consumption due the COVID-19 outbreak is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a positive blood culture was reported in 13.2% (n=17) of the patients, greater than other studies, like in Engsbro, et al, were the presence of blood stream infections was demonstrated in 5.3% of their critically III patients (n=12) [6]; in Yu and cols that reported the presence of a positive blood culture in 6.5% of their patients; and Martinez-Guerra and cols. [7] they observed the presence of a blood stream infections on 29.1% of their population (n=32) being a coagulase negative staphylococci the most frequent cause in 40%, followed by Enterobacter complex in 20% with a 14.3% of AmpC producers pathogens, 2.9% Extended spectrum beta lactamases and 2.9% Pseudomonas aeruginosa multidrug resistant, nevertheless this last studies does not make difference between mild, moderate or critically III patients [7,8].…”
Section: Discussionmentioning
confidence: 86%